Differentiating math instruction common core mathematics in the 21st century classroom - Bender, William N. (Corwin, 2013)
This title blends the best of what technology has to offer with guidelines for meeting the objectives set forth by the common core. Every new innovation in math instruction is addressed: flipping math instruction; project-based learning; using Khan Academy in the classroom; educational gaming; teaching for deeper conceptual understanding